Wolverine and American Mythology: The Ultimate Anti-hero - Picón del Campo, Nuria (Journal of Artistic Creation and Literary Research, 2025)
The main aim of this project is to show the importance of graphic novels in American culture, as well as to analyze and justify the role of anti-heroes in a world where they match or even surpass the popularity of heroes, using as the main example the character known as Wolverine. An analysis of this character in terms of American literature and society, together with a brief review of the history of American superheroes, serves to demonstrate how Wolverine has become the ultimate American anti-hero.